REVITALISASI KOTA LAMA SURABAYA:: PENGARUH TERHADAP KONDISI SOSIAL DAN EKONOMI KOMUNITAS LOKAL (Cultoure: Jurnal Ilmiah Pariwisata Budaya Hindu, 2025)
The tourism sector in Indonesia, as one of the main pillars of the economy, has significant potential to drive economic development and create job opportunities. In this context, Kota Lama Surabaya, which was inaugurated as a historical and cultural tourism area on July 3, 2024, is the focus of this research. The revitalization of this area aims to enhance the welfare of the local community through the maintenance and restoration of historical buildings, as well as the creation of friendly and attractive public spaces. This study employs a descriptive qualitative method to analyze the impact of revitalization on the socio-economic conditions of the community surrounding Kota Lama Surabaya, focusing on changes in income, job opportunities, consumption patterns, and infrastructure. The findings indicate that revitalization has improved the quality of life for residents, strengthened social interactions, and created new business opportunities, although it also presents challenges related to social values. Community involvement in the management of the area is crucial to ensure the sustainability and alignment of tourism activities with local needs. This research is expected to provide insights for the development of more sustainable tourism in Kota Lama Surabaya.Keywords: Revitalization; Historical Tourism; Sustainable Tourism; Urban Heritage.
Keywords: Revitalization; Historical Tourism; Sustainable Tourism; Urban Heritage